DETERMINANT CAPITAL STRUCTURE OF BANKING COMPANY IN INDONESIA - Elly Astuti (KINERJA, 2018)
This study aims to reveal the factors that affect the capital structure of banking companies in Indonesia. The study of capital structure has been widely documented in Indonesia, but in some previous literature always take out banking companies because of its unique characteristics. Therefore, this research is expected to increase scientific knowledge about the determinant factor of capital structure. The analysis technique used in this research is linear regression with dependent variable: asset turnover, liquidity, collateral, company growth, risk, profitability and company size. The capital structure is proxied by debt to assets ratio with the separation between long term debt, short term debt and total debt. The result of the analysis shows that the determinant factor analyzed can influence the bank capital structure significantly.